Analisis Human Error Dengan Metode SHERPA Dan HEART Pada Budidaya Telur Burung Puyuh - Hendrawan, Aldi; Dutho Suh Utomo; Suwardi Gunawan (Jurnal Teknik Industri (JATRI), 2025)
Lovepuyuh UMKM is a business located in Bangun Rejo Village, Tenggarong Oppo District, Tenggarong City, East Kalimantan. This business is engaged in production related to quail such as meat, seeds and quail eggs. Based on LovePuyuh MSME data for each quail egg production process, 80% of the products are classified as perfect products. Meanwhile, 5% of the products were seriously damaged and the other 15% were moderately damaged. This research uses the method Systematic Human Error Reduction and Prediction Approach (SHERPA) and the Human Error Assessment and Reduction Technique (HEART) method. The results of this research show that human error can occur, namely that there are 14 things that can occur in the human error ceramic production process. Human error occurs in 5 main work processes in each sub-job. In the cage preparation process there are 3 human errors, in the breeding process there are 3 human errors, in the cage maintenance process there are 3 human errors, in the health inspection process there are 2 human errors, and in the harvesting process there are 3 human errors. Classification Errors The total work is divided into 9 errors in the action category (action errors), 3 errors in the checking category (checking errors), and 2 errors in the selection category (selection errors). The largest HEP value is found in the quail egg production process, namely in the cage temperature calculation sub-work with a value of 0.99 and the smallest HEP is in the seed type selection process with a value of 0.0000888. Potential errors The biggest problem occurs in the sub-work of cleaning cages from dirt, so special attention is needed from the operator to prevent errors.